(untitled) (Development Service Industry Management, 2025)
The content and structure of a strategic management mechanism for developing leadership skills of self-employed persons are proposed. The core elements of such mechanism include: leadership skills, axioms, principles, typical mistakes, tools, team organization/outsourcing, and support for developing leadership skills. The mechanism of strategic management for developing leadership skills of self-employed persons contains theoretical and practical levels. Components for each of the designated levels of this mechanism are suggested. A description is provided for each of the proposed elements of the strategic management mechanism for developing leadership skills of self-employed persons. The leadership skills considered for self-employed persons include: strategic vision, analytical vision, readiness to make decisions, responsibility, resilience, high emotional intelligence, integrity (honesty), development of other team members, adaptability, critical thinking, readiness to delegate, communication skills (communicativeness), objective self-assessment, deep industry knowledge, ability to overcome conflicts, optimism, time management, and basic financial qualification. The following are considered as axioms within the strategic management mechanism for developing leadership skills of self-employed persons: unity of the subject and object of managerial influence, time as a key resource, necessity of leadership skills for self-employed persons, necessity of managing development of leadership skills, duration of the period for forming leadership skills of self-employed persons, risks of professional and personal "burnout", orientation towards demanded leadership skills, and impossibility of fully delegating development of these skills. A set of principles for the strategic management mechanism of developing leadership skills for self-employed persons is proposed, and the content of each of these principles is disclosed. These principles include: goal orientation (purposefulness), planning, specialization, legality (lawfulness), preemptive (leading) nature, efficiency (economy), individual responsibility, individual customization (tuning), ability to evolute, permanence (consistency), flexibility, and adaptability to needs. Typical mistakes within the strategic management mechanism for developing leadership skills of self-employed persons are identified and described.